Pengaruh Penguasaan Mufrodat Terhadap Kemampuan Membaca Kitab Kuning Santri di Pondok Pesantren An-Nidhom - Abdullah Syihabuddin; Septi Gumiandari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Mastery of the Arabic mufrodat is the main challenge for students in Islamic boarding schools, especially in reading the yellow book which requires a deep understanding of the rules of the Arabic language. This phenomenon reflects the importance of vocabulary mastery in supporting the reading skills of classical Arabic texts. This study aims to (1) analyze the mastery of mufrodat of An-Nidhom Islamic Boarding School students, (2) analyze the ability to read the yellow book, and (3) describe the influence of mastery of mufrodat on the ability to read the yellow book. This study uses a qualitative approach with a descriptive design. Data was collected through interviews and questionnaires involving 18 students as samples. The analysis was carried out with the stages of data reduction, data presentation, and conclusion drawn. The results of the study showed that (1) most of the students had mastery of mufrodat in the categories of very good (55.5%) and good (44.5%), (2) the ability to read the yellow book of students was shown through the accuracy of reading based on the rules of nahwu and shorof, understanding of the content of the reading, and the ability to express the content of the reading systematically, and (3) there was a significant positive influence between the mastery of mufrodat and the ability to read the yellow book, which is supported by grammatical rule-based learning and the active role of Ustadz in the teaching process. This study emphasizes the importance of strategies to strengthen mufrodat learning to improve the ability to read the yellow book in Islamic boarding schools.